2013
DOI: 10.1155/2013/462968
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recovery Uveitis Masked as an Endogenous Endophthalmitis in a Patient with Active CMV Retinitis

Abstract: Cytomegalovirus (CMV) retinitis may occur in profoundly immunocompromised patients and be the initial AIDS-defining infection. The incidence and prevalence of CMV retinitis has declined substantially in the era of highly active antiretroviral therapy (HAART); nevertheless, it remains a leading cause of ocular morbility. We report the case of a 40-year-old man with blurred vision and pain in the right eye, three weeks after the initiation of effective HAART treatment. Ocular examination revealed a panuveitis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…IRU usually develops in patients with inactive CMV retinitis but it rarely can occur in eyes with active CMV retinitis, especially at the onset of inflammation [25]. IRU usually affects all eyes with CMV retinitis, but sometimes patients had IRU in only one of the two eyes with CMV retinitis (26.3% of those with bilateral retinitis in the study of Kempen et al) [26].…”
Section: Definition Of Irumentioning
confidence: 99%
See 1 more Smart Citation
“…IRU usually develops in patients with inactive CMV retinitis but it rarely can occur in eyes with active CMV retinitis, especially at the onset of inflammation [25]. IRU usually affects all eyes with CMV retinitis, but sometimes patients had IRU in only one of the two eyes with CMV retinitis (26.3% of those with bilateral retinitis in the study of Kempen et al) [26].…”
Section: Definition Of Irumentioning
confidence: 99%
“…The severity of inflammation is related to various factors such as extent of CMV retinitis, amount of intraocular CMV antigen, degree of immune constitution, and previous treatment [ 19 ]. IRU usually develops in patients with inactive CMV retinitis but it rarely can occur in eyes with active CMV retinitis, especially at the onset of inflammation [ 25 ]. IRU usually affects all eyes with CMV retinitis, but sometimes patients had IRU in only one of the two eyes with CMV retinitis (26.3% of those with bilateral retinitis in the study of Kempen et al) [ 26 ].…”
Section: Definition Of Irumentioning
confidence: 99%
“…Additionally, there was a positive serum and cerebrospinal fluid CMV load in his previous hospitalisation, and, most importantly, active CMV retinitis with IRU has been reported 18 19. We also thought that anti-CMV therapy should be started to prevent the reactivation of CMV retinitis when using systemic steroids in patients with IRU.…”
Section: Discussionmentioning
confidence: 91%
“…8 Many studies reported the incidence of CMV papilitis found less than 10% in CMV retinitis cases. CMV retinitis accounts for 75-85% of CMV disease and over 90% 14 in an active CMV retinitis infection. In his report the patient had good visual outcome, from hand movement with good projection to 5/12 after induction doses of oral valganciclovir.…”
Section: Discussionmentioning
confidence: 99%